Structural behavior of cold-formed steel semi-oval hollow section beams. (15th April 2019) - Chen, Man-Tai; Young, Ben
Highlights: Beam behavior of cold-formed steel semi-oval hollow sections was studied. Three-point and four-point bending tests were conducted on semi-oval hollow sections. Numerical analyses were performed on semi-oval sections under constant moment. Modified Direct Strength Method and Continuous Strength Method are proposed. Abstract: The structural behavior of cold-formed steel semi-oval hollow sections under bending was studied through experimental and numerical investigation. The semi-oval hollow sections investigated in this study were cold-formed from hot-extruded seamless carbon steel circular hollow sections. A total of 20 beams was tested for both four-point and three-point bending configurations. The sections were bent about the major axis in both positive and negative directions. The tests were replicated numerically by means of rigorous finite element analyses. Based on the validated finite element model, an extensive parametric study was conducted on 198 beam specimens with a wide range of cross-section geometries subjected to pure bending about the major axis in both positive and negative directions. The current design rules for steel structures, such as Australian/New Zealand standards, European codes as well as American and the North American specifications, do not cover the design of semi-oval hollow sections. Therefore, the ultimate flexural capacities of beam specimens obtained from the test program and numerical investigation were only compared with the design strengths predicted by the Direct Strength Method and the Continuous Strength Method. The applicability and reliability of these two design methods were evaluated through reliability analysis. The results show that the existing design methods provide quite conservative and scattered design strength predictions for cold-formed steel semi-oval hollow section beams. In this study, modifications on the Direct Strength Method and the Continuous Strength Method are proposed, which provide better design strength predictions with improved accuracy in a reliable manner.